A Longitudinal Analysis of Cumulative Risks, Cumulative Promotive Factors, and Adolescent Violent Behavior - Stoddard, Sarah A. (2012)
This study examined the effects of cumulative risk and promotive factors on violent behavior across the high school years of adolescence in a sample of predominately African American urban adolescents (n = 750). Cumulative risk and promotive factor indices represented individual characteristics, and peer, parental, and familial influences. Using growth curve modeling, we describe trajectories of cumulative risk and promotive factors and test the associations between the time-varying cumulative risk and promotive factor indices and violent behavior. Higher risk was associated with higher levels of violent behavior. Higher levels of promotive factors were associated with less violent behavior and moderated the association between risk and violent behaviors. The results support the risk-protective model of resiliency. Implications for prevention are discussed.